Achieved versus Ascribed Master Status in a Positive Deviance Profession. Issue 6 (3rd June 2022) - Heckert, Druann; Heckert, Alex; Morooka, Hideki
ABSTRACT: Positive deviance is an increasingly accepted concept in sociology. The clergy constitute a quintessential positive deviance occupation as they are held to idealized norms. They have a master status applied to them; still, they have an achieved status as they freely choose their profession, feeling it to be a calling. On the other hand, the family of clergy also have a master status applied to them based on idealized norms. They, however, usually do not choose this ascribed status. Interviews were conducted with clergy and family members of clergy. Clergy accepted that they felt called to enter the profession. For family members, the master status is primarily ascribed. They often felt judged (on idealized norms) and felt pressure to conform to the idealized norms. The pressure can lead to guilt and isolation. While some acknowledge the positive impact on their lives, the ascribed nature of the status presents challenges.